Analysis Of The Effect Of El Niño La Nina And Sea Level Temperatures On Chlorophyll-A Concentrations In The Waters Of The Maluku Sea: - Pesoth, Christianto; Rimper, Joice R.T.S.L; Warouw, Veibe; Mantiri, Rose O. S. E.; Sumilat, Deiske Adeliene (Sam Ratulangi University, 2024)
Global weather phenomena cannot be separated from the interaction between the ocean and the atmosphere. El Nino and La Nina are phenomena that were related to the interaction of the sea and the atmosphere which affects many aspects, including the fertility of waters. Indicators of the fertility of water could be determined from the distribution of sea surface temperature and chlorophyll-a concentration. This study aims to analyze variations in the distribution of sea surface temperature and chlorophyll-a in the Maluku Sea when the El Nino and La Nina phenomena are activated. The results showed that when the El Nino phenomenon was activated, there was a decrease in sea surface temperature and an increase in the concentration of chlorophyll-a from normal conditions. Besides, when the La Nina phenomenon was activated, there was an increase in sea surface temperature and a decrease in the concentration of chlorophyll-a from normal conditions. Spatial interpretation when El Nino and La Nina are activated showed low values with a distribution indicating the mixed proceed for the sea surface temperature parameter and showed higher values with an even distribution for the chlorophyll-a parameter. Keywords: Sea Surface Temperature, Chlorophyll-a, El Nino, La Nina. Abstrak Fenomena cuaca secara global tidak bisa lepas kaitannya dengan interaksi antara laut dan atmosfer. El Nino dan La Nina merupakan salah satu fenomena yang berkaitan dengan interaksi laut dan atmosfer yang berpengaruh terhadap banyak aspek termasuk kesuburan suatu perairan. Indikator kesuburan suatu perairan dapat ditentukan dari distribusi suhu permukaan laut dan konsentrasi klorofil-a. Penelitian ini bertujuan untuk menganalisa variasi distribusi suhu permukaan laut dan klorofil-a di perairan Laut Maluku saat fenomena El Nino dan La Nina aktif. Hasil penelitian menunjukkan bahwa saat fenomena El Nino aktif terjadi penurunan suhu permukaan laut dan peningkatan konsentrasi klorofil-a dari kondisi normal. Sebaliknya saat fenomena La Nina aktif terjadi peningkatan suhu permukaan laut dan penurunan konsentrasi klorofil-a dari kondisi normal. Interpretasi spasial saat El Nino dan La Nina aktif menunjukkan nilai yang rendah dengan sebaran yang menunjukkan proses mixing untuk parameter suhu permukaan laut, dan menunjukkan nilai yang lebih tinggi dengan sebaran merata untuk parameter klorofil-a. Kata kunci: Suhu Permukaan Laut, Klorofil-a, El Nino, La Nina.